Photo - catalytic effect on shape memory polymers : polyvinyl alcohol ( PVA / PVOH ) with Gold Nanoparticles ( AU ) - Chan, Jeffrey Kok Fie (2015)
In the recent years, shape memory polymers have been widely used in a variety of applications especially in the medical field. Research has been done on polyvinyl alcohol (PVA) cross-linked with glutaraldehyde (GA) and they are shown to exhibit shape memory effect. However, not much research has been done on the photo-catalytic effect on PVA cross-linked with GA in which light stimulus is used to activate the shape memory effect of this PVA. Therefore, this project will focus on the shape memory effect of PVA with gold (AU) nanoparticles and the PVA will be cross-linked with GA. PVA samples cross-linked with GA but without the gold nanoparticles will act as controls in this project. Various characterisation tests like the Differential Scanning Calorimetry (DSC), X-ray Diffraction (XRD) Spectroscopy and Ultraviolet-Visible (UV-vis) Spectroscopy are carried out to investigate the thermal, structural and optical properties of the PVA samples respectively. Three experiments, using light as the stimulus will also be carried out to investigate the shape memory effect of the PVA samples. From the results obtained, it is concluded that the PVA samples with gold nanoparticles exhibited shape memory effect by recovering from their deformed shape back to their original shape when exposed to the light source but not the PVA samples without the gold nanoparticles. This is due to the Surface Plasmon Resonance (SPR) effect of the gold nanoparticles. The higher the concentration of gold nanoparticles, the better is the shape memory effect of the PVA samples when exposed to light.